Augusto Conte diputado. Entre la Democracia Cristiana y el Movimiento de Derechos Humanos - Fabris, Mariano; Ferrari, Marcela (Anuario de Historia de América Latina, 2019)
The article focusses on the performance of the Christian Democrat Augusto Conte during the first years of democratic reconstruction in Argentina. From a microanalytical perspective on an individual scale, it is possible to shed light on the complex network of political-social actors of the early eighties around two central problems of this particular situation: the revision of the dictatorial past and the prosecution of those responsible for the violations of human rights. The follow-up of this trajectory makes it possible to elucidate the scope and limitations faced by this deputy as representative of the human rights movement in Parliament against the government’s strategies, the demands and tensions that human rights organizations went through and the conflicts that arose in the Christian Democratic Party in whose name he assumed the position.